Meaning of Free Intraperitoneal Fluid in Small‐Bowel Obstruction: Preliminary Results Using High‐Frequency Microsonography in a Rat Model. (1st May 2014) - Iacobellis, Francesca; Berritto, Daniela; Belfiore, Maria Paola; Di Lanno, Imma; Maiorino, Manuela; Saba, Luca; Grassi, Roberto
Abstract : Objectives: The aim of this study was to detect the onset, evolution, and meaning of extraluminal free fluid in a rat model of small‐bowel obstruction using high‐frequency microsonography. Methods: Small‐bowel obstruction was surgically created in 8 rats divided into 2 groups of 4 rats each. All rats were examined by high‐frequency microsonography to monitor the evolution of small‐bowel obstruction and the abdominal sonographic findings. In group 2 rats, the obstruction was resolved 2 hours after surgery. Results: In all rats, free peritoneal fluid was detected just near the obstructed loop after 1 hour and in the hepatorenal recess after 2 hours. These features progressively increased in the following hours in group 1 rats. In group 2, the amount of free fluid decreased shortly after removing the obstruction. Conclusions: Free fluid is an early finding in small‐bowel obstruction, and the increase or decrease of its amount is correlated with the worsening or resolution of the obstruction.